Creativity and Innovation and Its Effect on Entrepreneurial Performance of Family Businesses in Eastern Nigeria - Ogbara, Samuel; Chukwunwa, Chinedu (PT.KARYA GEMAH RIPAH, 2025)
This study examines the impact of creativity and innovation on the entrepreneurial performance of family businesses in Onitsha North, Anambra State. Family businesses play a significant role in Nigeria's economy but face challenges such as limited resources, competition, and inadequate innovation. Using a quantitative research design, data were collected from 100 family businesses across various sectors, with a sample size of 80 determined through Taro Yamane's formula. Findings revealed a strong positive correlation between creativity, innovation, and entrepreneurial performance. Specifically, businesses that prioritized creativity and innovation reported higher revenue growth, improved market share, and enhanced customer satisfaction. The results showed that 75% of respondents had implemented new ideas or products in the past year, with 70% acknowledging significant positive impacts on performance. However, 60% of respondents identified funding and resource constraints as major barriers to innovation. Hypothesis testing using Chi-Square analysis confirmed that creativity and innovation individually and jointly impact entrepreneurial performance significantly (p < 0.05). The study highlights the critical role of creativity and innovation as valuable resources that enhance entrepreneurial performance in family businesses. Despite their recognition of these factors, challenges such as limited resources hinder full utilization. The findings provide insights for policymakers and practitioners on strategies to foster creativity and innovation in family businesses. Recommendations include increased investment in employee training, process improvement, and access to financial support to enhance performance and sustainability. This study contributes to the body of knowledge by addressing the nexus of creativity, innovation, and entrepreneurial performance in the Nigerian context.